Elemental mass movement in the geothermal system at Surtsey, S Iceland - Daníel Bergur Ragnarsson 1995- (2019)
Massaflutningur frumefna í jarðhitakerfum er mikilvægur til þess að skilja verkanirnar á bakvið ummyndun bergs, Myndun síðsteinda í jarðhitakerfinu í Surtsey gefur til kynna massaflutning frumefna og ummyndun bergs. Þessar hreyfingar á efni má reikna með gögnum úr borleiðöngrum í eynni árið 1979 og 2017. Sem sýna fram á skerðingu frumefna sem leysast upp í sjó en auðgun frumefna sem koma úr sjónum og í móbergið. Sem gefur til kynna myndbreytingu á þeim 38 árum milli borana. Elemental mass movement of geothermal systems is important to understand the mechanisms behind rock alteration. Secondary mineral findings in samples from boreholes in the geothermal system in Surtsey indicate elemental mass movement and rock alterations in the system. These movements are quantifiable with temporal data from two drilling campaigns in 1979 and 2017. Which shows depletion of elements going into seawater and enrichment of elements being added to the rock from the seawater. Implying a degree of tuff alteration in the 38 years between observations.